Young People, Social Inclusion & Social Action (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
The lives of young people are constantly under scrutiny. The social construction of their roles and responsibilities within civil society appears to be increasingly controlled by a dominant discourse promoted by the state.  They are consistently presented within a contradictory framework that describes them as a perceived threat to social order and the moral fabric of society as well as a pillar of the nation’s future.  Their relationship to an adult dominated society has become an arena for constant attention from the state and reactive intervention by youth workers and other service providers. The various pathways through the transition from adolescence to adulthood have become indicators of social exclusion and to a greater extent deviancy. Young people’s lifestyles and their progression through the pathways of transition are measured against a framework of milestones and objectives constructed by the central and local state to measure their success and failure (Scottish Executive 1999). The potential role of young people as citizens within civil society is pre-determined by their position within the transition towards adulthood.  The pathways from adolescence present young people with increasingly extended routes within which decisions have to be made and numerous obstacles overcome.  The transition from youth to adult has subsequently become prolonged and often fractured